Liquid phase exfoliation of talc: effect of the medium on flake size and shape - Sousa, Samuel M.; Morais, Helane L. O.; Santos, Joyce C. C.; Barboza, Ana Paula M.; Neves, Bernardo R. A.; Pinto, Elisângela S.; Prado, Mariana C. (Beilstein Journal of Nanotechnology, 2023)
Industrial applications of nanomaterials require large-scale production methods, such as liquid phase exfoliation (LPE). Regarding this, it is imperative to characterize the obtained materials to tailor parameters such as exfoliation medium, duration, and mechanical energy source to the desired applications. This work presents results of statistical analyses of talc flakes obtained by LPE in four different media. Talc is a phyllosilicate that can be exfoliated into nanoflakes with great mechanical properties. Sodium cholate at two different concentrations (below and at the critical micelar concentration), butanone, and Triton-X100 were employed as exfoliation medium for talc. Using recent published statistical analysis methods based on atomic force microscopy images of thousands of flakes, the shape and size distribution of nanotalc obtained using the four different media are compared. This comparison highlights the strengths and weaknesses of the media tested and hopefully will facilitate the choice of the medium for applications that have specific requirements.
Keywords: 2D materials; atomic force microscopy; liquid phase exfoliation; nanomaterials; talc